2015
DOI: 10.1136/archdischild-2014-306427
|View full text |Cite
|
Sign up to set email alerts
|

Acute and late coronary outcomes in 1073 patients with Kawasaki disease with and without intravenous γ-immunoglobulin therapy

Abstract: Objective To explore acute and late coronary outcomes and their risk/modifiers in patients with Kawasaki disease (KD). Design Retrospective study. Setting and patients 1073 patients with KD identified from a tertiary care medical centre (1980-2012; 8677 patient-years). Main outcome measures The acute coronary severities and late outcomes (survival free of coronary aneurysm persistence and ischaemia) were assessed. Results Coronary arterial lesions occurred in 40.6% of cases at their acute febrile stages, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 20 publications
(18 reference statements)
5
59
0
1
Order By: Relevance
“…In a Taiwanese study evaluating KD patients including 27 patients with giant CAA (≥8 mm), the same result was found [9]. On the other hand, a recent study reviewing 90 US patients with giant CAA based on z-scores, found that in 19% of the patient with giant CAA regression occurred [10].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In a Taiwanese study evaluating KD patients including 27 patients with giant CAA (≥8 mm), the same result was found [9]. On the other hand, a recent study reviewing 90 US patients with giant CAA based on z-scores, found that in 19% of the patient with giant CAA regression occurred [10].…”
Section: Discussionsupporting
confidence: 57%
“…Our finding that regression mainly takes place in the first 5 years is supported by earlier studies. Lin et al found a 5-year persistence rate of 46% for medium-sized CAA with little regression after [9]. Kato et al, studying a group of patients with CAA of all sizes, found that 90% of regression occurred within the first 2 years [11].…”
Section: Discussionmentioning
confidence: 99%
“…96 Long-term prognosis in children with coronary artery aneurysms is predicted in part by coronary artery size at 1 month of illness, with the 10-year ischemia event-free and aneurysm persistence probability being 87.5% and 20.6%, respectively. 113 Successful surgical treatment (eg, CABG) of late sequelae of symptomatic coronary artery stenoses has been described. 114 …”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 99%
“…The number of coronary aneurysms in our cohort of patients was relatively high (19.6%), similar to those in the group without IVIG treatment, where the incidence of coronary aneurysms was between 20% and 25% [24]. The infusions with IVIG in Bulgaria started in 1998, but only in a limited number of patients.…”
Section: Treatment Of Patients With Kawasaki Diseasementioning
confidence: 65%